CONTRACEPTIVE METHODS OFFERED BY SUS (UNIFIED HEALTH SYSTEM): KNOW TO PROTECT YOURSELF (CIPEEX, 2025)
ABSTRACT: Contraception is a cost-effective strategy that allows men and women to planthe timing of their children’s arrival. The SUS (Brazilian Unified Health System) offers differentmethods, such as hormonal (oral and injectable), barrier (condoms and diaphragm),intrauterine devices (IUD), and definitive sterilization (tubal ligation and vasectomy). WithinSUS, contraceptive methods are chosen according to the patient’s preference, who receivesinformation during reproductive planning consultations in Primary Care. The Ministry ofHealth guides services through manuals and protocols. For contraceptive surgery (tuballigation or vasectomy), it is necessary to meet legal requirements, sign a consent form, andwait 60 days before the procedure, ensuring time for reflection. Method efficacy is also animportant criterion in the choice. Among injectables, medroxyprogesterone acetate and thecombination of norethisterone enanthate + estradiol valerate are available. The choice ofmethod should be free and informed, according to the patient’s reality and preference. It isimportant to highlight that condoms are the only method that, in addition to preventingpregnancy, also protect against Sexually Transmitted Infections (STIs). Contraceptionrepresents a fundamental advance in reproductive health, offering people the possibility toplan motherhood and fatherhood in a safe and conscious way. Among the available methods,internal and external condoms stand out as the main physical barriers to fertilization, which, inaddition to preventing pregnancy, are the only ones that also protect against STIs. Thecontraceptive pill, one of the most widely used methods in the world, symbolizes a milestonein women’s autonomy. Composed of synthetic hormones similar to estrogen andprogesterone, it prevents ovulation and modifies cervical mucus, although it hascontraindications that must be assessed by a physician. Another alternative is the injectablehormonal contraceptive, administered monthly or quarterly, which works similarly to the pillbut with greater practicality. Also hormonal, the subdermal implant is a long-term option:inserted under the skin of the upper arm, it continuously releases substances that preventovulation and hinder sperm from reaching the egg. Among non-hormonal methods, theIntrauterine Device (IUD) stands out, especially the copper IUD, which triggers aninflammatory reaction in the uterus capable of eliminating sperm. With long duration and highefficacy, it can remain effective for up to ten years without requiring continuous use or dailydiscipline. Finally, there are definitive methods: tubal ligation and vasectomy. Both aresurgical procedures that interrupt the path of gametes, ensuring permanent efficacy. Preciselybecause of their irreversibility, these methods require professional follow-up, family planningsessions, and careful evaluation. Thus, the diversity of available options enables eachindividual or couple to choose the method most appropriate to their reality, always based oninformation, autonomy, and health care.
Keywords: contraceptives; Hormones; Methods; effectiveness